2012
DOI: 10.1098/rspb.2012.0638
|View full text |Cite
|
Sign up to set email alerts
|

Complex effects of temperature on mosquito immune function

Abstract: Over the last 20 years, ecological immunology has provided much insight into how environmental factors shape host immunity and host–parasite interactions. Currently, the application of this thinking to the study of mosquito immunology has been limited. Mechanistic investigations are nearly always conducted under one set of conditions, yet vectors and parasites associate in a variable world. We highlight how environmental temperature shapes cellular and humoral immune responses (melanization, phagocytosis and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
192
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 141 publications
(201 citation statements)
references
References 87 publications
7
192
0
Order By: Relevance
“…Based on previous studies (Bauerfeind & Fischer, 2014; Murdock et al., 2012; Triggs & Knell, 2012), hemocyte density was expected to decrease at the higher temperature treatments. Instead, we saw numbers increase linearly with increasing temperature, something that has previously only been shown in Plodia when larvae are under additional environmental stressors (Triggs & Knell, 2012).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Based on previous studies (Bauerfeind & Fischer, 2014; Murdock et al., 2012; Triggs & Knell, 2012), hemocyte density was expected to decrease at the higher temperature treatments. Instead, we saw numbers increase linearly with increasing temperature, something that has previously only been shown in Plodia when larvae are under additional environmental stressors (Triggs & Knell, 2012).…”
Section: Discussionmentioning
confidence: 98%
“…While increasing temperature tends to increase the rate of biochemical processes, this does not necessarily extend to all aspects of physiology, and increasing temperature may not positively correlate with improved immune competence (Angilletta, Huey, & Frazier, 2010; Murdock et al., 2012; Suwanchaichinda & Paskewitz, 1998). …”
Section: Introductionmentioning
confidence: 99%
“…Effects of temperature on immune and life-history traits Previous studies both from evolutionary ecology and biological pest control have, in general, shown that even a modest rise in temperature makes the hosts more resistant to infections by microbes and parasites (Thomas andBlanford, 2003, Adamo andLovett, 2011), although the response is not necessarily linear, highlighting the significance of measurements done in a range of temperatures (Murdock et al, 2012). In our study, the encapsulation responses of beetles reared at 18 1C were the highest, and the encapsulation ability was the lowest at the highest temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Temperature has been shown to affect immune responses in a variety of insects, including beetles, crickets, butterflies and Drosophila (fruit flies). Focusing on mosquito vectors, a few studies have investigated the effect of temperature on mosquito immune responses; Suwanchaichinda & Paskewitz [93] showed that the melanization response in Anopheles gambiae progressively decreases as temperatures increase, while Murdock et al [94] investigated the response of cellular and humoral immunity to changes in temperature. In the latter study, a complex picture emerged, with melanization, phagocytosis and an antimicrobial peptide (AMP) defensin expression peaking at 188C, whereas nitric oxide synthase expression peaked at 308C.…”
Section: The Role Of Climate In Insect Vector-pathogen Interactionsmentioning
confidence: 99%
“…B 370: 20130551 response to changes in ambient temperature. The study in reference [94] demonstrates how the immune gene profile of a vector at one ambient temperature can be completely altered at a different temperature. This could impact the vectorial capacity of insect vectors of malaria and other pathogens.…”
Section: The Role Of Climate In Insect Vector-pathogen Interactionsmentioning
confidence: 99%